Determinants of employee wellbeing among women lawyers in Selangor - Roslina, Zainal (2020)
As employees are the backbone of any company, their wellbeing is therefore crucial. Employee wellbeing undeniably becomes an important aspect for every organization. Thus, the main aim of the study is to examine the relationship of work family conflict, organizational support and reward on the Employee’s wellbeing among women lawyers in Selangor. The study is conducted on 235 women employees from various firms. To analyses the data that been collected, Statistical Package for Social Science (SPSS) used in order to examine the relationship of the data collected. Based on the multiple regression analysis, found that work family conflict and reward do not have significant relationship with employee wellbeing compared to organizational support. Finally from the researcher point of view, the organization should play a significant role in order to maintain employee wellbeing because it ought to bring multiple benefits to the organization.